Feasibility of using sodium alginate for improving structural quality of sweet dahi - Islam, MN; Arefin, S; Sarker, MAH; Akhter, S; Habib, R (Bangladesh Journal of Animal Science, 2016)
Dahi is a popular fermented milk product with higher nutritional value and significant therapeutic properties. The objective of the present study was to use sodium alginate as stabilizer to monitor the feasibility of using for improving structural quality of sweet dahi. Dahi were prepared using 0.4%, 0.6%, 0.8% and 1% sodium alginate. One control sample was made with no stabilizer to judge the other treated samples. All the samples were analyzed for organoleptic and chemical qualities .Significant difference was found in case of smell & taste score (p<0.05), body & consistency (p<0.01), color (p<0.01). Highest (p<0.05) smell and taste score was found at 0.6% sodium alginate treated dahi. In case of body & consistency 0.6% sodium alginate showed better results. In case of color, 0.6% level of sodium alginate (p<0.01) showed nearly similar result as dahi with no sodium alginate. Significant (p<0.01) differences were found among the treatments in case of composition of dahi samples, except for the fat content, which showed insignificant (p>0.05) difference. Total solids, ash and protein content of dahi samples were increased after addition of sodium alginate. From the above analysis 0.6% sodium alginate was found to be better and it can be concluded that sodium alginate can be used as stabilizer to improve the structural quality of dahi. Bang. J. Anim. Sci. 2016. 45 (2): 66-72